Classroom Interaction and Communication Strategies in Learning English as a Foreign Language - Mateja Dagarin (ELOPE, 2004)
The article focuses on the development of interaction in a foreign language classroom. Teachers can help students to develop their interaction skills and students themselves can apply various strategies to become effective communicators in a foreign language. Firstly, different teacher and student roles are presented. Secondly, different classroom organisation types for encouraging interaction among different participants in the classroom are described. Next, Flander’s Interaction Analysis Categories (FIAC) and Byrne’s model for classroom interaction are given as two models upon which to analyse classroom interaction and plan activities for developing it. In the final part some communication strategies are described and exemplified in detail. If all the techniques and strategies are put into practice, one can expect an improvement in classroom interaction and furthermore in everyday-life situations when students communicate with foreign speakers.